EVALUATION OF ARTHROSCOPIC SURGERY OUTCOMES FOR SHOULDER IMPINGEMENT SYNDROME (Vietnam Journal of Community Medicine, 2026)
Background: This study was conducted with two objectives: (1) To investigate the features on X-ray and magnetic resonance imaging (MRI) in patients with shoulder impingement syndrome (SIS); and (2) To evaluate the outcomes of treating SIS with arthroscopic surgery.Methods: A prospective descriptive case series was performed on 30 patients diagnosed with SIS who had failed conservative treatment. The study was conducted at Khanh Hoa General Hospital from March 2024 to December 2025. Treatment outcomes were assessed using the VAS pain scale, and the Constant and UCLA functional scores, both pre- and post-operatively.Results: The mean age of the patients was 55.8 ± 8.6 years. On imaging, type II acromion was the most prevalent (60%), followed by type III (23.3%). The mean acromial angle was 26.6 degrees, and the mean acromiohumeral distance was 6 mm. Post-surgery, the mean VAS score significantly decreased from 6.2 to 0.5 (p < 0.01). According to the Constant score, 93.4% of patients achieved good and excellent results. Based on the UCLA score, 90% of patients achieved good and excellent results. No major complications were recorded.Conclusion: Arthroscopic surgery is a safe and effective method for the treatment of shoulder impingement syndrome, providing significant pain relief, improving shoulder function, and having a low rate of complications.
Keywords: Shoulder impingement syndrome, arthroscopic surgery, acromioplasty, Constant score, UCLA score